2018 IEEE Symposium Series on Computational Intelligence (SSCI) 2018
DOI: 10.1109/ssci.2018.8628810
|View full text |Cite
|
Sign up to set email alerts
|

A Stacked Autoencoder Neural Network based Automated Feature Extraction Method for Anomaly detection in On-line Condition Monitoring

Abstract: Condition monitoring is one of the routine tasks in all major process industries. The mechanical parts such as a motor, gear, bearings are the major components of a process industry and any fault in them may cause a total shutdown of the whole process, which may result in serious losses. Therefore, it is very crucial to predict any approaching defects before its occurrence. Several methods exist for this purpose and many research are being carried out for better and efficient models. However, most of them are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 32 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…The latest development of feature extraction methods based on self-encoders provides methods for them, but they are mainly limited to the field of image and audio processing. Based on self-encoders and online sequential learning networks, Roy et al developed an automatic feature extraction method for online status monitoring 33 . Experiments show that the method performs well.…”
Section: Discussionmentioning
confidence: 99%
“…The latest development of feature extraction methods based on self-encoders provides methods for them, but they are mainly limited to the field of image and audio processing. Based on self-encoders and online sequential learning networks, Roy et al developed an automatic feature extraction method for online status monitoring 33 . Experiments show that the method performs well.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the concept of deep learning, traditional AEs were extended as SAE by adding multiple layers, usually larger than 2 layers, to form the deep structure of an AE. The detailed content of SAE can be found in [19,20]. x  .…”
Section: Autoencoder-based Network For Clusteringmentioning
confidence: 99%
“…This implementation ensures a real-time, low-cost solution due to the parallel processing capability of FPGA. A stacked autoencoder neural networkbased automated feature extraction method for anomaly detection in online condition monitoring was presented in [20]. The authors showed that the proposed method could achieve very high detection accuracy for determining the bearing health states, and their simple design method is promising for easy hardware implementation.…”
Section: Introductionmentioning
confidence: 99%